Examine digital ecosystem in the Malaysian construction supplychain - Low, Ming Chi (2023)
Digital ecosystem is a complex network of interlinked companies, where people make use of digital devices and application software on a secured platform to exchange digital content. The National Construction Policy in Malaysia aims to establish a conducive infrastructure development ecosystem and targeted digitalizing half of the industry’s cycle by 2030. This research examines the current state of digital ecosystem in the Malaysian construction supply-chain and explores its underpinning issues. Four key constituents of the digital ecosystem namely device, network, content, and application are synthesized from the literature reviewed. 41 close-ended questionnaire statements embracing the four key constituents were constructed to explore the availability of digital infrastructure in construction organizations. Another 40 statements were used to assess the digital knowledge and talent of the construction community. Three open-ended questions were included for the respondents to share the subjective issues in digitalization encounters. The quantitative data collected from 200 respondents have undergone reliability analysis, Friedman test, Chi-square test and Kruskal-Wallis H test generalized the significant findings that social collaboration applications are more prevalent in the organization and the construction community is more competent with social collaboration application than smart technologies. The construction supplychain faced seven (7) major digitalization issues of high network latency, lack of digital knowledge and skills, inadequate digital infrastructure, intricate software and technology, immature common data environment, expensive software subscription fees, and fixed cultural mindset. These findings offer a snapshot of the current digital ecosystem in the Malaysian construction supplychain which enable the industry practitioners to preempt the issues; regulators to facilitate the industry by developing alleviation policies, permit researchers to conduct further investigation and educational institutions to improve the related course curriculum.